2016
DOI: 10.1681/asn.2014121217
|View full text |Cite
|
Sign up to set email alerts
|

HANAC Syndrome Col4a1 Mutation Causes Neonate Glomerular Hyperpermeability and Adult Glomerulocystic Kidney Disease

Abstract: Hereditary angiopathy, nephropathy, aneurysms, and muscle cramps (HANAC) syndrome is an autosomal dominant syndrome caused by mutations in COL4A1 that encodes the a1 chain of collagen IV, a major component of basement membranes. Patients present with cerebral small vessel disease, retinal tortuosity, muscle cramps, and kidney disease consisting of multiple renal cysts, chronic kidney failure, and sometimes hematuria. Mutations producing HANAC syndrome localize within the integrin binding site containing CB3[IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 56 publications
(66 reference statements)
4
53
0
Order By: Relevance
“…21 In the present study, we provide new insights into the mechanisms of the skeletal muscle involvement, which is a major feature of this syndrome. Striated muscle BM contains from the a1a2(IV) collagen IV network.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…21 In the present study, we provide new insights into the mechanisms of the skeletal muscle involvement, which is a major feature of this syndrome. Striated muscle BM contains from the a1a2(IV) collagen IV network.…”
Section: Discussionmentioning
confidence: 82%
“…Dex41/Dex41 mice that lack extracellular a1a1a2(IV) trimers, the Col4a1 p.G498V mutation did not completely abolish the assembly and secretion of the mutant protein in the muscle as well as in the kidney, 21 which may explain the less severe phenotype of HANAC Col4a1eG498V mutant mice. In vitro observations also showed that the degree of mutant a1(IV) intracellular retention was influenced by the location of the mutations, those located at the C-terminal part of the protein were associated with higher intracellular accumulation and more severe organ defects.…”
Section: Col4a1-related Muscle Diseasementioning
confidence: 97%
See 2 more Smart Citations
“…In addition to the Col4a1;Col4a2 null mutation 14 , and a Col4a1 conditional mutation 101, 110 , there are presently 17 mutations reported in Col4a1 and Col4a2 that cause pathology in multiple tissues and organs 16, 17, 100, 104 (Fig. 1).…”
Section: ) Genotype–phenotype Correlations In Col4a1 and Col4a2 Mutamentioning
confidence: 99%